Testing RESTful APIs – Use Case: RESTful API for Solving Multidimensional Time–Independent Schrödinger Equation - Dimoski, Davor; Koteska, Bojana; Pejov, LJupcho; Mishev, Anastas (CEUR-WS.org, 2022)
Many of enterprise software applications today are developed using a service-oriented architecture (SOA) where web services, especially microservices play a fundamental role. A RESTful web service is a lightweight and scalable web service that provides data over the Internet via an API using the HTTP protocol. Testing of a RESTful API is challenging because the user inputs are sequences of HTTP requests to a remote server and the server responses are also in HTTP format. In this paper, we aim to analyse ten different tools for testing RESTful API web services and provide tool comparisons first based on the request support and second based on multiple functionalities-implementation, platforms, languages, testing techniques, and supported imports. Taking into account this analysis and tools possibilities, we perform testing on RESTful API service for solving multidimensional time-independent Schrödinger equation using the Hermite DVR approach. The findings show that not all tests could be run on all testing tools since some of them do not offer ready-made assertions for validating the response time or HTTP body content or there is no option for validating the HTTP body.
Keywords: REST API; RESTful web service; Testing tools; Schrödinger equation